Study on the threshold for superposed deformation of simply supported bridge creep and track slab upwarp in high-speed railway. (December 2022) - Li, Guolong; Gao, Mangmang; Yang, Fei; Wei, Zilong; Yang, Jingjing
Based on long-term inspection data about track geometric irregularity of 32 m-span simply supported girder bridge in China Railway High-Speed for nearly 10 years, it is found that there is continuous periodic track longitudinal level (TLL) with different wavelengths, thereinto, simply supported girder bridges creep and ballastless track slab upwarp are the primary reasons. Moreover, there are two types of variation trends for bridge creep of 32 m simply-supported bridges with ballastless track, that is, stable type and increasing type, and the maximumV pp ll (the peak-to-peak value of track longitudinal level) is 7.1 mm for track longitudinal level caused by bridge creep, and the maximumV pp ll caused by upwarp deformation of ballastless track slab is 3.2 mm. Hence, this paper investigated the effects on running performance and structure service performance of random track irregularity and additional track irregularity caused by bridge creep, track slab upwarp deformation or superposition of both, a three-dimensional finite element model of vehicle-track-bridge for dynamic simulation calculation was established, the threshold values for bridge creep and track slab deformation under 350 km/h were proposed based on running performance and structure service performance. Finally, research results show that bridge creep influences on the ride comfort significantly, but running safety barely. Due to the short wavelength of TLL, the track slab upwarp deformation affects both the ride comfort and running safety heavily. The car bodies are more sensitive to bridge creep and produce mainly low-frequency vibration, but the rate of wheel load reduction is more sensitive to the track deformation and shows the high-frequency vibration. For 32 m simply supported bridges without track slab deformation, theV pp ll caused by bridge creep should be limited to 7 mm, and 9 mm in difficult situations. When theV pp ll caused by bridge creep is small (less than 5 mm), theV pp ll caused by track slab upwarp deformation must be less than 4 mm. When both deformations exist simultaneously, theV pp ll caused by superposition deformations of both should not exceed 10 mm, with track slab upwarp deformation not exceeding 4 mm. In the presence of both structural deficiencies, it is suggested that the track slab deformation must be eliminated when it is difficult to eliminate the bridge creep.